Speech Production Analysis of an Autism Character in the Movie “Rain Man” by Barry Levinson (A Psycholinguistic Study) - Sugara, Ria Dewi Hudayani; Alawiyyah, Anisa; Saparianingsih, Ria; Septiani, Arini Nur (Candradimuka: Journal of Education, 2025)
This research aims to find out what are the type of autism experience by Raymond in the movie “Rain Man” and to find out how speech production of autistic experience by Raymond. The method used in this research is qualitative and the object studied is the main actor in the film "Rain Man" named Raymond. The researcher collected data from the film and from dialogue transcripts. After the data is obtained then transferred to a computer and listened to many times, then transcribed into conversation. Data were analyze using the theory from Turkington & Anan (2007) to analyze the type of autism and Scovel (1998) to analyze speech production experience by Raymond. Based on this theory, it is known that the main character in the film "Rain Man", namely Raymond, has autistic (high-function), and Raymond has difficulty producing language. He repeated his words, the same phrase, or sentence from the other person when he or she cannot understand the meaning of the conversation. This paper recommended for readers to understand language production in someone with autism, especially for those who have had contact with autistic people in their surrounding environment. And for future researchers who conduct research in the same field, especially those who have the same interest in language disorders in autistic children as a reference or comparison that may be relevant to their research.